PERAN DISIPLIN KERJA DALAM MEMEDIASI DIKLAT (PENDIDIKAN DAN PELATIHAN) SERTA MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEHUTANAN PROVINSI BALI - Anak Agung Sagung Agustiari; Putu Ngurah Suyatna Yasa; I B Agung Dharmanegara (Jurnal Ekonomi dan Bisnis Jagaditha, 2017)
The tittle of this reaserch is â€œThe Mediating Role in Labor Discipline Training (Education and Training) and Work Motivation on Employee Perfomanceâ€. Aims of the research is to know influence about Diklat to Performance, Motivate to Performance , Diklat to Discipline , Motivate to Discipline and also Discipline to Performance. Totally of officer population On Duty Forestry Province of Bali counted 80 people, but which used as a sample only 30 people as according to officer which have got the Diklat. Analysis model use program of smart PLS (Partial Least Square). This Research find that Diklat having an effect on positive and significant to Performance , Motivation have an effect on positive but not significant to Performance, Diklat having an effect on positive and significant to Discipline, Motivation have effect on positive and significant to Discipline, and also Discipline have effect on positive and significant to Performance. Directly analysis and indirectly conclude that direct influence of Diklat compared to bigger than direct influence trought to Discipline.